The Gambia : Request for Disbursement Under the Rapid Credit Facility, Cancellation of the Extended Credit Facility Arrangement, and Proposal for a Staff-Monitored Program-Staff Report; Press Release; and Statement by the Executive Director for the Gambia. - International Monetary Fund. African Dept. (Washington, D.C. : International Monetary Fund, 2015)
KEY ISSUES Background. The Gambian economy is facing urgent balance of payments needs triggered mostly by the impact of the regional Ebola outbreak on tourism. Although the country remains Ebola free, the regional outbreak is expected to cut by more than half tourism receipts for the 2014/15 season. During 2014?15, the impact of the shocks on the balance of payments, offset in part by lower global fuel prices, is estimated to be USD 40 million (over 5 percent of 2015 GDP). Policy slippages and persistent financial difficulties in public enterprises have exacerbated the problems and pushed The Gambia's ECF arrangement off track. In their Letter of Intent the authorities have notified the Fund of their decision to cancel the arrangement. Request. The authorities are requesting support under the RCF-in an amount of SDR 7.775 million or equivalent to 25 percent of quota-to cope with the urgent balance of payments needs and a one-year staff-monitored program (SMP) to guide policy implementation before returning to a successor ECF arrangement, provided policies remain on track. Main policy commitments. The authorities have taken a number of upfront policy actions. The approved 2015 budget envisages lowering net domestic borrowing (NDB) to 1 percent of GDP in 2015 from 12u percent in 2014, anchored by a set of revenue and expenditure measures, and complemented by some USD 22 million in external budget support. The authorities have taken steps to resolve the financial problems of key public enterprises and intend to take measures to secure their medium-term fiscal consolidation and poverty reduction objectives. Staff's view. Staff supports the authorities' request. Staff views the package of measures articulated in the attached letter of intent as representing a considerable effort. The RCF disbursement would augment the authorities' own strong adjustment efforts, help catalyze additional donor financing, and give the authorities the time needed to develop their medium-term adjustment plans. The SMP will provide the Gambian authorities an opportunity to establish a track record before moving to a successor ECF to which they aspire. A period of monitoring will also allow the time needed to assess the impact of the shocks fully and hence better tailor the objectives of a successor ECF arrangement.
Off-Campus Access: No User ID or Password Required
On-Campus Access: No User ID or Password Required
Mode of access: Internet